Evaluation of a PCR-based lateral flow device for detecting Aspergillus and Candida species from clinical specimens - Ariff Khalid; Jacinta Santhanam; Mohd Nizam Tzar; Ang-Lim Chua; Sharifah Fadilah Abdul Wahid; Wan Rahiza Wan Mat; Raha Abd Rahman; Petrick Periyasamy (Heliyon)
Objectives: The diagnosis of invasive fungal diseases (IFDs) is time consuming and lacks sensitivity. In this research a rapid and easy to use immunochromatography-based DNA biosensor system was developed to detect Candida and Aspergillus pathogens at genus level, while specifically detecting Candida glabrata, Candida krusei and Aspergillus terreus. This system combines multiplex PCR with a lateral flow assay (LFA) dipstick. Methods: Three separate multiplexed PCR reactions were designed together with a testing algorithm, using biotin, digoxigenin and Tamra fluorophore-labelled fungal internal transcribed spacer universal fungal primers, fungal genera-specific primers, and species-specific primers to produce labelled PCR products that were detected on the LFA dipstick. The LFA dipstick, in a modified sandwich format, utilises immobilised antibodies complementary to the fluorophore labels on the PCR products, and gold nanoparticles to form a visible red line that indicates the presence of the targeted fungus. To validate the developed system, 203 clinical samples suspected of fungal infection were collected from two hospitals in Kuala Lumpur and tested. Results: The limits of detection of the multiplexed PCR were in the range of 5–100 CFU/mL for fungal spiked human blood samples. Against the clinical diagnosis of proven or probable IFDs, the findings show that the LFA system produced a high specificity of 99.4 % while the sensitivity was only moderate at 47.8 % due to the difficulty of extracting fungal DNA from blood samples. The positive and negative predictive values however were promising at 91.7 % and 93.7 %, respectively. Conclusion: The developed LFA system has great potential for further refinement to be used as a new tool in the detection of IFDs.